Dampak Kebijakan BPOM Terhadap Keamanan Obat Sirup: Evaluasi Pasca Kejadian Gagal Ginjal Akut Pada Anak - Mazaya Raini Nurmaliza; Alya Salsabilah; Meutya Zahra Saphira; Muhammad Hafizh Azzuraiqi; Januar Ariyanto (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Cases of acute kidney injury (AKI) in children in Indonesia in 2022 became a matter of national and medical concern. A thorough investigation conducted by the Ministry of Health, the World Health Organization (WHO), and the National Agency of Drug and Food Control (BPOM) revealed that the main cause of this incident was contamination by the toxic compounds ethylene glycol (EG) and diethylene glycol (DEG) found in children's syrup medications, with levels far exceeding the safe threshold. These findings raised questions about the effectiveness of the national drug monitoring system, particularly regarding excipients that had escaped comprehensive testing. This study aims to critically evaluate the impact of BPOM's policies following the incident on the safety of children's syrup medications. Using a qualitative approach through literature review, this research examines the effectiveness of supervision, the implementation of new regulations, and the challenges within Indonesia’s drug monitoring system. The analysis shows that although BPOM has enacted significant policy reforms such as the recall of contaminated products, the establishment of strict contaminant limits, and the requirement for laboratory testing of every batch of excipients there are still considerable obstacles. These include limited laboratory capacity, constrained supervisory resources, and the economic impact on the pharmaceutical industry. This study recommends strengthening a risk-based regulatory system and cross-sector collaboration as preventive measures to ensure the safety of children's medicines in the future